(Re)construindo sentidos: os discursos sobre a formação do professor de língua portuguesa no Brasil - Cressoni, Luciana Aleva (Universidade Federal de São Carlos, 2015)
This research aims to understand the dominant circulating senses and, therefore, appear as a true effect on being a Portuguese language teacher in Brazil. Understanding that the senses are linked to the work of ideology and language policies, which as part of the subjectivation forms (in an unconscious process) of teachers, try to hold individuals responsible for their profession to be (dis)articulator of failure of language teaching. The senses of Portuguese as a national language works to produce the effect of the difficulties of Portuguese and here we will present and analyze how these constructions were possible throughout the history of the schooling of our foreign national language. We understand that the issues related to language teaching are not linguistic issues, but political is that we present our work so that we understand that to say about the Portuguese teacher as a teacher who is always exposed to lack in the schooling processes is the condition of never be allowed to be a producer of his own linguistic knowledge. Teachers of Portuguese not authorized to produce their knowledge are discursively constituted by the lack, a kind of lack of capacity to produce this knowledge by the legal demand of only reproducing the strategies of education legitimized by the public policies on literacy and the teaching of the language understanding that this is a way of dismantling them, thus disarticulating the teaching of language in public schools.
(Re) constructing senses: the speeches on the training of the teacher of portuguese language in Brazil
Keywords: Análise do discurso; Formação de professores; Políticas linguísticas; Discourse analysis; Teacher training; Language policy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO